2014
DOI: 10.1038/npp.2014.44
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Rescue of Cortical Synaptic and Network Potentiation in a Mouse Model for Fragile X Syndrome

Abstract: Fragile X syndrome, caused by the mutation of the Fmr1 gene, is characterized by deficits of attention and learning ability. In the hippocampus of Fmr1 knockout mice (KO), long-term depression is enhanced whereas long-term potentiation (LTP) including late-phase LTP (L-LTP) is reduced or unaffected. Here we examined L-LTP in the anterior cingulate cortex (ACC) in Fmr1 KO mice by using a 64-electrode array recording system. In wild-type mice, theta-burst stimulation induced L-LTP that does not occur in all acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
82
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(90 citation statements)
references
References 68 publications
8
82
0
Order By: Relevance
“…The ERK/MAPK and mTOR pathways are two critical signaling pathways that regulate protein synthesis in the brain and have been implicated in the pathophysiology of fragile X (3,4). We focused on the neocortex, because neocortical network activity is enhanced in fragile X (20), and proteinsynthesis-dependent synaptic plasticity is impaired in the fragile X cortex (21). ERK/MAPK signaling is initiated by activation of Ras, which phosphorylates the protein kinase MEK.…”
Section: Erk But Not Mtor Signaling Is Elevated In the Cortex Of Fmr1 Komentioning
confidence: 99%
“…The ERK/MAPK and mTOR pathways are two critical signaling pathways that regulate protein synthesis in the brain and have been implicated in the pathophysiology of fragile X (3,4). We focused on the neocortex, because neocortical network activity is enhanced in fragile X (20), and proteinsynthesis-dependent synaptic plasticity is impaired in the fragile X cortex (21). ERK/MAPK signaling is initiated by activation of Ras, which phosphorylates the protein kinase MEK.…”
Section: Erk But Not Mtor Signaling Is Elevated In the Cortex Of Fmr1 Komentioning
confidence: 99%
“…A major finding in brain samples of Fmr1 -/-mice is the abnormally high levels of GSK3b, a key kinase shown to play critical roles in several molecular pathways, including MAPK, Cyclin, Akt, and the canonical Wnt/b-catenin signaling pathway [26,[45][46][47]. The role of GSK3b, as part of the canonical Wnt/bcatenin signaling pathway, was shown to be important during adult neurogenesis in the murine hippocampus [29] and in FXS pathology in Fmr1 -/-mice [27,28].…”
Section: Expression Of Gsk3b and B-catenin In Fx-hnpcsmentioning
confidence: 99%
“…While altered hippocampal long-term potentiation (LTP) is not typical in Fmr1 KO mice (Godfraind et al, 1996), when it is observed the deficit is in LTP stability (Lauterborn et al, 2007). Reduced or abolished LTP is observed in neocortex and amygdala (Larson et al, 2005; Zhao et al, 2005; Shang et al, 2009; Chen et al, 2014). However, the functional changes that link dysregulated translation to impaired cognition are unknown, and a theory is lacking.…”
Section: Introductionmentioning
confidence: 99%